2016
DOI: 10.4191/kcers.2016.53.5.521
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the Proton Conduction Limiting Barriers and Trajectories in BaZr0.875Y0.125O3 Due to the Presence of Other Protons

Abstract: Kinetic Monte Carlo (KMC) and graph searches show that proton conduction limiting barriers and trajectories in BaZr 0.875 Y 0.125 O 3 are affected by the presence of other protons. At 1000 K, KMC limiting conduction barriers increase from 0.39 eV to 0.45 eV as the proton number is increased. The proton-proton radial distribution begins to rise at 2 Å and peaks at 4 Å, which is half the distance expected, based on the proton concentration. Density functional theory (DFT) calculations find proton/proton distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…In the present scenario involving 4 protons (x ¼ 4/8), it is reasonable to observe this effect to be even more preponderant. While our results are in full accordance with the results by Gomez et al 66 on the concept of extended distortions, we suggest that these distortions are, at least partially, dynamical rather than static at room temperature, as they span both the oxygen atom dynamics and the extended proton arrangement. Whatever the case, the concept of extended distortions is consistent with the coexistence of numerous local proton congurations and thus the apparent large inhomogeneous broadening of the vibrational spectra of 50In/BZO.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present scenario involving 4 protons (x ¼ 4/8), it is reasonable to observe this effect to be even more preponderant. While our results are in full accordance with the results by Gomez et al 66 on the concept of extended distortions, we suggest that these distortions are, at least partially, dynamical rather than static at room temperature, as they span both the oxygen atom dynamics and the extended proton arrangement. Whatever the case, the concept of extended distortions is consistent with the coexistence of numerous local proton congurations and thus the apparent large inhomogeneous broadening of the vibrational spectra of 50In/BZO.…”
Section: Discussionsupporting
confidence: 93%
“…lower n(O-H) frequency, in a recent computational work on Y-doped BaZrO 3 . 66 This work, which was based on models with a single dopant (x ¼ 1/8) and two protons, suggested that the protons tend to pair, in agreement with previous results from Bork et al 67 on SrTiO 3 , and that the proton-proton vicinity affects the hydrogen bond strength. According to these works, the effect of one proton on another one is not a mere direct proton-proton interaction, but rather is driven by local lattice distortion.…”
Section: Discussionsupporting
confidence: 89%
“… 38 Kinetic Monte Carlo (KMC) simulations, which simulated proton dynamics using 96 binding sites with a 12.5% dopant concentration, have predicted activation energies of 38 kJ mol –1 for a single proton 45 and 43 kJ mol –1 when eight protons were included in the simulation. 46 In these simulations, the protons spend a significant amount of time in Y–OH–Z sites but travel between these sites through perpendicular and planar sites. These activation energies are closer to the values of 40.5 and 45.0 kJ mol –1 determined experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, kinetic Monte Carlo (KMC) associated with DFT calculations has shown that proton conduction can be hampered by the presence of other protons [210], as suggested by calculation of proton transporting energy barriers at high temperature in doped BZO. It is relevant to mention that oxidation and hole conductivity can be affected by polaronic contribution in the doped state of BZO perovskite [175].…”
Section: Theoretical Studies On Bzo Proton Conductormentioning
confidence: 99%